INEFEKTIVITAS PROGRAM FOOD ESTATE KABUPATEN GUNUNG MAS: SEBUAH ANALISIS DIAGRAM POHON - Surbakti, Agnes Margaretha; Gebrena, Muhammad Rafli; Jannah, Lina Miftahul (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2023)
The Indonesian government has made efforts to create food security to ensure that all people obtain food in the appropriate quantity and quality, such as through the Food Estate Program. One of the food estate programs is carried out in Gunung Mas Regency, Central Kalimantan. However, in practice, the food estate in Gunung Mas Regency still experiences various ineffectiveness in its implementation. Based on these problems, this article aims to analyze the implementation of the Gunung Mas Regency food estate program as an effort to realize the sustainability of food security. The article uses a qualitative descriptive analysis method. Data collection techniques were carried out with document studies in the form of secondary data derived from various sources such as online media news, electronic publication data, and other credible sources. Data analysis was carried out using the tree diagram method to identify the cause and effect of the food estate program. The results of this paper conclude that there are still several ineffectiveness problems in the food estate program in Gunung Mas Regency, such as the top-down approach in program implementation, limited agricultural supporting facilities and infrastructure, and efforts to proletarize farmers. Therefore, a collaboration-based approach is key in achieving sustainable food security.